The treasure house: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Treasure House" is a story about the journey of discovering inner wealth and the true value of life. It often focuses on themes such as the importance of wisdom, love, and community over material riches. The protagonist usually learns that the greatest treasures are not physical possessions, but rather the relationships and experiences that enrich one$1 (Bs life.s